MCAM/CD146 Signaling via PLCγ1 Leads to Activation of β1-Integrins in Memory T-Cells Resulting in Increased Brain Infiltration - Zondler, Lisa; Herich, Sebastian; Kotte, Petra; Körner, Katharina; Schneider-Hohendorf, Tilman; Wiendl, Heinz; Schwab, Nicholas; Zarbock, Alexander (Frontiers in Immunology, 2020)
Multiple sclerosis is a chronic auto-inflammatory disease of the central nervous system affecting patients worldwide. Neuroinflammation in multiple sclerosis is mainly driven by peripheral immune cells which invade the central nervous system and cause neurodegenerative inflammation. To enter the target tissue, immune cells have to overcome the endothelium and transmigrate into the tissue. Numerous molecules mediate this process and, as they determine the tissue invasiveness of immune cells, display great therapeutic potential. Melanoma cell adhesion molecule (MCAM) is a membrane-anchored glycoprotein expressed by a subset of T-cells and MCAM+ T-cells have been shown to contribute to neuroinflammation in multiple sclerosis. The role of the MCAM molecule for brain invasion, however, remained largely unknown. In order to investigate the role of the MCAM molecule on T-cells, we used different in vitro and in vivo assays, including ex vivo flow chambers, biochemistry and microscopy experiments of the mouse brain. We demonstrate that MCAM directly mediates adhesion and that the engagement of MCAM induces intracellular signaling leading to β1-integrin activation on human T-cells. Furthermore, we show that MCAM engagement triggers the phosphorylation of PLCγ1 which is required for integrin activation and thus amplification of the cellular adhesive potential. To confirm the physiological relevance of our findings in vivo, we demonstrate that MCAM plays an important role in T-cell recruitment into the mouse brain. In conclusion, our data demonstrate that MCAM expressed on T-cells acts as an adhesion molecule and a signaling receptor that may trigger β1-integrin activation via PLCγ1 upon engagement.